International Rangelands Congress 2025: Advancing Private Sector Investment in Rangeland Restoration - Flintan, Fiona E. (International Livestock Research Institute, 2025)
The International Rangelands Congress is held every four years to promote the interchange of scientific and technical information on all aspects of rangelands: research, planning, development, management, extension, education and training. Its most recent gathering in Adelaide, Australia in early July 2025 was a welcome opportunity to get feedback from the good and the great of rangelands science and practice on the global rangeland standard and monitoring framework being developed with support from the GEF-funded project STELARR (Sustinable Investment for Large-Scale Rangeland Restoration). It also contributed to the momentum of discussions on the role of private sector investment in rangeland restoration—a hot topic for Congress attendees!